Lipoprotein(a): a risk factor for atherosclerosis and an emerging therapeutic target - Di Fusco, Stefania Angela; Arca, Marcello; Scicchitano, Pietro; Alonzo, Alessandro; Perone, Francesco; Gulizia, Michele Massimo; Gabrielli, Domenico; Oliva, Fabrizio; Imperoli, Giuseppe; Colivicchi, Furio (Heart (British Cardiac Society), 2023)
Lipoprotein(a) (Lp(a)) is a complex circulating lipoprotein, and increasing evidence has demonstrated its role as a risk factor for atherosclerotic cardiovascular disease (ASCVD) and as a possible therapeutic target. Lp(a) atherogenic effects are attributed to several potential mechanisms in addition to cholesterol accumulation in the arterial wall, including proinflammatory effects mainly mediated by oxidised phospholipids. Several studies have found a causal and independent relationship between Lp(a) levels and cardiovascular risk. Furthermore, several studies also suggest a causal association between Lp(a) levels and calcific aortic valve stenosis. Available lipid-lowering agents have at best moderate impact on Lp(a) levels. Among available therapies, antibody proprotein convertase subtilisin/kexin type 9 inhibitors are the most effective in reducing Lp(a). Potent Lp(a)-lowering treatments that target LPA expression are under development. Lp(a) level measurement poses some challenges due to the absence of a definitive reference method and the reporting of Lp(a) values as molar (nanomoles per litre (nmol/L)) or mass concentrations (milligrams per decilitre (mg/dL)) by different assays. Currently, Lp(a) measurement is recommended to refine cardiovascular risk in specific clinical settings, that is, in individuals with a family history of premature ASCVD, in patients with ASCVD not explained by standard risk factors or in those with recurrent events despite optimal management of traditional risk factors. Patients with high Lp(a) levels should be managed with more intensive approaches to treat other modifiable cardiovascular risk factors. Overall, this review focuses on Lp(a) as an ASCVD risk factor and therapeutic target. Furthermore, it reports practical recommendations for Lp(a) measurement and interpretation and updated evidence on Lp(a)-lowering approaches.